REVIEW: POTENSI MIKOREMEDIASI LOGAM BERAT - Kurniawan, Andri; Ekowati, Nuraeni (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2016)
Heavy metals contamination is a main issue which has negative impacts to environment and organisms. Various methods have been developed to reduce such pollutants, including utilization of organismsâ capability in order to minimize the contamination. Mycoremediation is one of remediation process in contaminated environment using fungi and its reduction mechanisms, involving intracellular, as well as extracellular system. There are some species of fungi that are frequently used as remediator agents, for example Aspergillus sp., Fusarium sp., Penicillium sp., Phanerochaete sp., Trichoderma sp. There are some methods that have been used for heavy metal reduction mechanisms such as biosorption, bioaccumulation, bioprecipitation, bioreduction, and bioleaching.Keywords: Mycoremediation, fungi, heavy metal, biosorption, bioaccumulationÂ ABSTRAK Kontaminasi logam berat adalah suatu permasalahan utama yang berdampak negatif bagi lingkungan dan juga makhluk hidup. Berbagai metode telah dikembangkan untuk mereduksi cemaran, termasuk memanfaatkan kemampuan organisme untuk meminimalkan kontaminan tersebut. Mikoredemiasi adalah salah satu proses remediasi cemaran di lingkungan dengan melibatkan fungi beserta mekanisme reduksinya, baik secara intraselular maupun ekstraselular. Beberapa jenis fungi yang sering dijadikan agen remediator antara lain Aspergillus sp., Fusarium sp., Penicillium sp., Phanerochaete sp., Trichoderma sp. Beberapa prinsip yang digunakan untuk menghilangkan logam berat antara lain biosorpsi, bioakumulasi, biopresipitasi, bioreduksi, dan bioleaching.Â Kata kunci: Mikoremediasi, fungi, logam berat, biosorpsi, bioakumulasi